Security strategies in Linux platforms and applications - Jang, Michael H.; Messier, Ric. (2017)
"The Second Edition of Security Strategies in Linux Platforms and Applications opens with a discussion of risks, threats, and vulnerabilities. Part 2 discusses how to take advantage of the layers of security and the modules associated with AppArmor and SELinux. Part 3 looks at the use of open source and proprietary tools when building a layered security strategy"--
Security threats to Linux -- Basic components of Linux security -- Basic security : facilities through the boot process -- User privileges and permissions -- Filesystems, volumes, and encryption -- Every service is a potential risk -- Networks, firewalls, and more -- Networked filesystems and remote access -- Networked application security -- Kernel security risk mitigation -- Managing security alerts and updates -- Building and maintaining a security baseline -- Testing and reporting -- Detecting and responding to security breaches -- Best practices and emerging technologies.
ISC-2017
Includes bibliographical references and index.
Keywords: Linux; Operating systems (Computers); Computer security